Makna Gramatikal Pada Novel Cinta Dua Kodi Karya Asma Nadia - Indana Zulfa Rommadonia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The word semantics or in English semantic etymologically comes from the Greek sema in its nominative form which means 'sign' or in its verb form samaino which means 'mark' or 'mean' or 'symbolise'. Indonesian must be used properly in accordance with the Indonesian language order that has been regulated and systemised. According to Chaer 2012: 266 that a complete sentence is formed from language units that have the highest position is discourse. Grammatical meaning is the meaning that is present as a result of grammatical processes such as affixation processes, reduplication processes, and composition processes.